The Balancing of Peroxynitrite Detoxification between Ferric Heme-Proteins and CO2: The Case of Zebrafish Nitrobindin - Giovanna De Simone; Andrea Coletta; Alessandra di Masi; Massimo Coletta; Paolo Ascenzi (MDPI AG, 2022)
Nitrobindins (Nbs) are all-β-barrel heme proteins and are present in prokaryotes and eukaryotes. Although their function(s) is still obscure, Nbs trap NO and inactivate peroxynitrite. Here, the kinetics of peroxynitrite scavenging by ferric Danio rerio Nb (Dr-Nb(III)) in the absence and presence of CO2 is reported. The Dr-Nb(III)-catalyzed scavenging of peroxynitrite is facilitated by a low pH, indicating that the heme protein interacts preferentially with peroxynitrous acid, leading to the formation of nitrate (~91%) and nitrite (~9%). The physiological levels of CO2 dramatically facilitate the spontaneous decay of peroxynitrite, overwhelming the scavenging activity of Dr-Nb(III). The effect of Dr-Nb(III) on the peroxynitrite-induced nitration of L-tyrosine was also investigated. Dr-Nb(III) inhibits the peroxynitrite-mediated nitration of free L-tyrosine, while, in the presence of CO2, Dr-Nb(III) does not impair nitro-L-tyrosine formation. The comparative analysis of the present results with data reported in the literature indicates that, to act as efficient peroxynitrite scavengers in vivo, i.e., in the presence of physiological levels of CO2, the ferric heme protein concentration must be higher than 10−4 M. Thus, only the circulating ferric hemoglobin levels appear to be high enough to efficiently compete with CO2/HCO3− in peroxynitrite inactivation. The present results are of the utmost importance for tissues, like the eye retina in fish, where blood circulation is critical for adaptation to diving conditions.